ChemInform Abstract: Synthetic Approaches to Glycophthalocyanines. Issue 23 (10th June 2014) - Lourenco, Leandro M. O.; Neves, Maria G. P. M. S.; Cavaleiro, Jose A. S.; Tome, Joao P. C.
Abstract Review: 110 refs.